2019
DOI: 10.1017/s002221511900183x
|View full text |Cite
|
Sign up to set email alerts
|

Facial artery musculomucosal flaps in oropharyngeal reconstruction following salvage transoral robotic surgery: a review of outcomes

Abstract: ObjectiveThere has been little reported on the transoral reconstructive options following salvage transoral robotic surgery. This paper describes the facial artery musculomucosal flap as a method to introduce vascularised tissue to a previously irradiated resection bed.MethodsA facial artery musculomucosal flap was used to reconstruct the lateral pharyngeal wall in 13 patients undergoing salvage transoral robotic surgery for oropharyngeal squamous cell carcinoma. Outcomes recorded include flap and donor site c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Of these, 51 articles were reviewed in full following screening and removal of duplicates. A total of 26 final studies met inclusion based on appropriateness of patient population, intervention performed, and outcome of interest adequately specified 15–40 . One study detailing reconstructive strategies of TORS defects was excluded due to lack of description regarding specific reconstructive modalities used in the patient cohort described 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 51 articles were reviewed in full following screening and removal of duplicates. A total of 26 final studies met inclusion based on appropriateness of patient population, intervention performed, and outcome of interest adequately specified 15–40 . One study detailing reconstructive strategies of TORS defects was excluded due to lack of description regarding specific reconstructive modalities used in the patient cohort described 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Such complications include exposure of vital structures, infection, delayed healing, and necrosis; introduction of healthy and well-vascularized tissue into these fields helps to minimize such morbidity and promotes positive functional outcomes. [9][10][11] The goals of oropharyngeal reconstruction are to provide adequate coverage of defects and associated structures while maintaining function, including velopharyngeal competence and swallowing. 10 In order to preserve the critical functions of the upper aerodigestive tract, careful consideration of all reconstructive options is required after TORS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flap reconstruction is a feasible alternative when a wide resection is needed to treat an oropharyngeal stenosis. Local flaps, such as buccal mucosal or facial artery musculomucosal flap, are the first available options in case of small-to-moderate-sized defects [ 21 24 ]. Larger defects require regional myocutaneous pedicled flaps or microvascular tissue transfer, which are all excellent options for wide oropharyngeal and hypopharyngeal reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The FAMM flap is commonly used for these indications and preferred for its large axis of rotation with ability to reach multiple areas within the oropharynx [36]. In a series of 13 patients undergoing salvage TORS for pT1–4 OPSCC reconstructed with the FAMM flap, all cases were successful without delayed wound healing, flap necrosis, or velopharyngeal insufficiency (VPI) [37 ▪ ]. Similar results were shown by Bonawitz et al [38] who reported flap success in all reconstructions which included four ipsilateral and one bilateral FAMM flaps.…”
Section: Recent Findingsmentioning
confidence: 99%